2022
DOI: 10.1186/s12862-022-01963-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental differences explain subtle yet detectable genetic structure in a widespread pollinator

Abstract: Background The environment is a strong driver of genetic structure in many natural populations, yet often neglected in population genetic studies. This may be a particular problem in vagile species, where subtle structure cannot be explained by limitations to dispersal. Consequently, these species might falsely be considered quasi-panmictic and hence potentially mismanaged. A species this might apply to, is the buff-tailed bumble bee (Bombus terrestris), an economically important and widespread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 149 publications
(187 reference statements)
1
1
0
Order By: Relevance
“…The initial introduction of just two or three queens to Tasmania likely led to the low genetic diversity we observed (Schmid‐Hempel et al., 2007; Figure 1, Figure S5 in Appendix S1; site pairwise F ST −0.0031 to 0.014, global F ST 0.005). However, our values are within the range of similarly low F ST values observed in invasive B. terrestris populations in Japan (pairwise F ST between two sites = 0.006, Nagamitsu & Yamagishi, 2009), native populations in continental Europe (global F ST = 0.005, Estoup et al., 1996) and Eastern Europe (global F ST = 0.006, Glück et al., 2022). Other Bombus species show similarly low genetic differentiation in continental Europe, such as B. lapidarius (global F ST = 0.003, Theodorou et al., 2018), B. hortorum in Belgium (global F ST = 0.010) and B. sylvarum (global F ST = 0.029, Maebe et al., 2019).…”
Section: Discussionsupporting
confidence: 80%
“…The initial introduction of just two or three queens to Tasmania likely led to the low genetic diversity we observed (Schmid‐Hempel et al., 2007; Figure 1, Figure S5 in Appendix S1; site pairwise F ST −0.0031 to 0.014, global F ST 0.005). However, our values are within the range of similarly low F ST values observed in invasive B. terrestris populations in Japan (pairwise F ST between two sites = 0.006, Nagamitsu & Yamagishi, 2009), native populations in continental Europe (global F ST = 0.005, Estoup et al., 1996) and Eastern Europe (global F ST = 0.006, Glück et al., 2022). Other Bombus species show similarly low genetic differentiation in continental Europe, such as B. lapidarius (global F ST = 0.003, Theodorou et al., 2018), B. hortorum in Belgium (global F ST = 0.010) and B. sylvarum (global F ST = 0.029, Maebe et al., 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies highlighted that isolation by environmental distance can occur in the absence of isolation by geographical distance or by resistance (Glück et al, 2022). Glück et al (2022) found that environmental differences accounted for over 30% of the genetic divergence observed among buff‐tailed bumblebee [ Bombus terrestris (Linnaeus, 1758)] populations across Romania and Bulgaria, although population structure was subtle ( F ST < 0.07) and not detected by Bayesian clustering. Environmental heterogeneity was suggested to act as a selective pressure against dispersers, which would result in a disruption in genetic connectivity whereby divergence in neutral markers can arise through genetic drift.…”
Section: Discussionmentioning
confidence: 99%